Penggunaan Media 'Bungnge Tallo' untuk Meningkatkan Pembelajaran Bilangan Kubik pada Siswa Sekolah Dasar - Arnold Jacobus (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objectives were to improve the six-grade pupils’ achievement in cubic numbers by means of ‘bungnge tallo APATI’ media. Ninety percent six-grade pupils achieved the mathematical concept on cubic numbers below the minimum mastery level in public elementary school 90 in Singkawang. The pupils’ low achievement was related to two reasons, namely: learning activities on mathematical concepts were not attractive to pupils, and learning methods applied by the teacher were not procedurally systematic in explaining the cubic numbers. This classroom action research was conducted in two cycles with four phases, namely: planning, action, observation and reflection. Analysis results show the pupils’ mean score = 45.0 in pre-cycle; mean score = 64.0 in cycle 1 with minimum mastery level at 67%; and mean score = 89.0 in cycle 2 with minimum mastery level at . 100%. In conclusion, the implementation of ‘bungnge tallo APATI’ media in learning mathematical concept on cubic numbers could be improved for the six-grade pupils at elementary school 90 in Singkawang.